Particulate plastics as a vector for toxic trace-element uptake by aquatic and terrestrial organisms and human health risk. (October 2019) - Bradney, Lauren; Wijesekara, Hasintha; Palansooriya, Kumuduni Niroshika; Obadamudalige, Nadeeka; Bolan, Nanthi S.; Ok, Yong Sik; Rinklebe, Jörg; Kim, Ki-Hyun; Kirkham, M.B.
Abstract: Particulate plastics in the terrestrial and aquatic environments are small plastic fragments or beads (i.e., 5 mm down to the nanometre range). They have been frequently referred to as 'micro-plastics' or 'nano-plastics'. Research has identified particulate plastics as a vector for toxic trace elements in the environment. The adsorption of toxic trace elements by particulate plastics may be facilitated by their high surface area and functionalized surfaces (e.g., through the attachment of natural organic matter). Other factors, such as environmental conditions (e.g., pH and water salinity), surface charge, and trace element oxidation status, also influence the adsorption of trace elements onto particulate plastics. Because of their small size and persistence, particulate plastics and the associated toxic trace elements are readily ingested and accumulated in many terrestrial and aquatic organisms. Thus, these plastics can have severe environmental consequences, such as the development of metal toxicity, within aquatic and terrestrial organisms. Humans could also become exposed to particulate plastics through food chain contamination and airborne ingestion. This review provides an overview of the sources of particulate plastics in the environment. To this end, we describe particulate plastics made of synthetic polymers, their origin, and characteristics with emphasis on how particulate plastics and associated toxic trace elements contaminate terrestrial and aquatic ecosystems. Future research needs and strategies are discussed to help reduce the environmental risks of particulate plastics as a potent vector for the transportation of toxic trace elements. Graphical abstract: Unlabelled Image Highlights: Particulate plastics include microplastics and nanoplastics. The review covers the ecological and human health impacts of particulate plastics. Trace-element-sorbed particulate plastics damage aquatic and terrestrial ecosystems. Dissolved organic matter facilitates trace element sorption onto particulate plastics. Particulate plastics pose human health threats by entering the food chain.